Fabrication and Characterization of Optical Devices on Lithium Niobate on Insulator Chips. (2016) - Saha, Soham; Yohanes, Siew Shawn; Jun, Deng; Danner, Aaron; Tsang, Mankei
Abstract: The high electro-optic coefficients and nonlinear coefficients of lithium niobate make it a highly promising material for optical modulator design, experiments in cavity quantum electrodynamics, and microwave photonics. The two most common techniques for photonic device fabrication on lithium niobate are titanium diffusion and proton exchange. However, due to very low refractive index contrast (usually less than 0.1), the waveguides formed through these processes have low mode confinement, high bending losses, and often, are not polarization independent, making it difficult to fabricate compact photonic structures on the material. Here, we report our new design: rib waveguide on lithium niobate on insulator chips. Lithium niobate on insulator chips contains a thin film of lithium niobate (thickness: ∼700 nm) adhering on an insulator substrate like SiO2 . Such devices provide good vertical and lateral index contrast and mode confinement. Also, because of the smaller waveguide widths attainable through etch based techniques, a greater control of the critical dimensions of devices is possible. We fabricated and characterized optical devices - waveguides, power splitters, and microring resonators on lithium niobate on insulator chips, employing robust fabrication techniques, namely EBL and ion milling. The structures were characterized in terms of propagation loss and quality factor. The fabricated structures showed good performance, and the fabrication techniques have potential for use in the mass manufacture of lithium niobate based optical devices.